Introduction to public administration in the Philippines : a reader - Bautista, Victoria A.; Alfiler, Ma. Concepcion P.; Reyes, Danilo R.; Tapales, Proserpina D. (Quezon City : University of the Philippines Press and the College of Public Administration, University of the Philippines, 1993)
Public Administration (PA) as a field of study has been growing in scope and content as well as changing in focus and style with the times and climes under which the practice of public administration operates.
1. Definition and scope of he study of public administration in the Philippines -- 2. Theories of bureaucracy and management -- 3. Development and development administration -- 4. Processes in public administration -- 5. Selected strategies in public administration -- 6. Public service values.
Includes bibliographical references and index.
Keywords: PUBLIC ADMINISTRATION